Joseph Stalin’s Death as Perceived by Soviet Citizens: Materials from the Kemerovo Region - Dmitry S. Morozov (СибСкрипт)
The article describes the way the population of the Kemerovo Region responded to the death of Joseph Stalin at mourning events as a projection of the Soviet myth. The author studied verbal and non-verbal reactions to identify the main concepts and patterns used by the local people to describe their psycho-emotional and mental state after receiving the news of Stalin’s death. The content and discourse analyses revealed the following verbal reactions: "shared loss" and "personal grief"; Stalin as a father figure, personifying the paternalistic attitude of the Soviet state towards its citizens; a connection between Stalin and the achievements of the entire country; appeals to citizens to strengthen production and political activity, to support the government; "immortality" of Stalin, his system, and Soviet achievements, and the "eternal significance" of his ideas. The non-verbal reactions included a total mobilization of political and production activities to consolidate people around the party and state institutions. In general, people’s response to Stalin’s death could be reduced to a reproduction of certain patterns that reflected the main ideologemes of the Soviet myth.